Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-long.325
|View full text |Cite
|
Sign up to set email alerts
|

How is BERT surprised? Layerwise detection of linguistic anomalies

Abstract: Transformer language models have shown remarkable ability in detecting when a word is anomalous in context, but likelihood scores offer no information about the cause of the anomaly. In this work, we use Gaussian models for density estimation at intermediate layers of three language models (BERT, RoBERTa, and XLNet), and evaluate our method on BLiMP, a grammaticality judgement benchmark. In lower layers, surprisal is highly correlated to low token frequency, but this correlation diminishes in upper layers. Nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Another line of probing work designs control tasks (Ravichander et al, 2021;Lan et al, 2020) to reverse-engineer the internal mechanisms of representations (Kovaleva et al, 2019;. However, in contrast to our work, most studies (Zhong et al, 2021;Li et al, 2021; focused on pre-trained representations, not fine-tuned ones.…”
Section: Related Workmentioning
confidence: 84%
“…Another line of probing work designs control tasks (Ravichander et al, 2021;Lan et al, 2020) to reverse-engineer the internal mechanisms of representations (Kovaleva et al, 2019;. However, in contrast to our work, most studies (Zhong et al, 2021;Li et al, 2021; focused on pre-trained representations, not fine-tuned ones.…”
Section: Related Workmentioning
confidence: 84%
“…To verify this possibility, we randomly sampled 1,000 sentences that contained "only N" and ever, respectively, from the Corpus of Contemporary American English (Davies, 2008-) and found their conditional probabilities are more or less balanced, e.g., P(ever|only) = 2.8% and P(only|ever) = 2.8%. In addition, Li et al (2021) recently showed by a layerwise model analysis that the effect of frequency information is strong only in the lower layers of Transformer language models like BERT but eventually decreases in the upper layers. Thus, we exclude the possibility that the unequal results for only in the two settings are simply an artifact of word frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…Note that there are also many probing papers without post-hoc classifiers (Zhou and Srikumar, 2021;Torroba Hennigen et al, 2020;Li et al, 2021). While many of these do not mention the term "probing", they nevertheless probe the intrinsics of deep neural models.…”
Section: Probing Methodsmentioning
confidence: 99%